Assessing the impact of libraries – the role of ISO 16439. Issue 1 (8th January 2018) - Creaser, Claire
Abstract : Purpose: Library impact and how to evaluate it has been debated for a number of years. While the activity – the busy-ness – of the library is now routinely measured and described, the difference the library makes is less tangible and harder to measure. Libraries in all sectors and worldwide are grappling with this issue, and the purpose of this paper is to summarise international standards available to support them. Design/methodology/approach: The first international standard concerning library impact, ISO 16439 Information and documentation – methods and procedures for assessing the impact of libraries, was published in 2014 after several years in development. Findings: The standard describes a range of methods for assessing library impact which have been used across the world in a variety of libraries in all sectors. Originality/value: This paper summarises the key methods described in the standard, and gives references for further reading.